Analysis of the Application of Blockchain in E-Business to Increase Consumer Trust - Harjoni Harjoni; Embrechts Xavier; Hide Haruka (Journal of Computer Science Advancements, 2024)
The rapid growth of e-business has led to increasing concerns about consumer trust due to issues such as data breaches, fraudulent activities, and lack of transparency. Blockchain technology, with its inherent characteristics of decentralization, immutability, and transparency, has emerged as a potential solution to address these challenges. This research aims to analyze the application of blockchain in e-business to enhance consumer trust, providing insights into its effectiveness and adoption barriers. The study employs a qualitative approach, combining a systematic literature review and expert interviews to gather comprehensive data. The research evaluates blockchain’s impact on key trust factors, such as data security, transaction transparency, and accountability within the e-business ecosystem. The findings reveal that blockchain significantly enhances consumer trust by ensuring data integrity, enabling secure and transparent transactions, and reducing intermediary dependency. However, challenges such as high implementation costs, technical complexity, and regulatory uncertainty hinder widespread adoption. The study concludes that blockchain technology has the potential to revolutionize trust mechanisms in e-business. To maximize its benefits, businesses must address implementation barriers and foster collaborations with regulatory authorities. Future research should explore blockchain’s integration with emerging technologies such as artificial intelligence and the Internet of Things to create a more robust e-business ecosystem.